Pengaruh Model Pembelajaran Kooperatif Group Investigation dengan Scaffolding Terhadap Pemahaman Konsep Fisika Siswa SMA - Herman Jufri Andi; Chariratul Umamah (Jurnal Penelitian Pembelajaran Fisika, 2018)
This study aims to identify how the influence of cooperative Group Investigation (GI) with scaffolding models for students physics concept ability. This research is a quasi-experimental study. The sample in this study was carried out by cluster random sampling technique with a pretest posttest control group design. The instrument used in this study is concept ability test in a multiple choice form consisting of 15 questions. the first sample was the experimental class (X-1) treated by the GI learning model with scaffolding and the second class was the control class (X-2) given cooperative learning treatment type Group Investigation (GI) with the number of each class of 20 students. Data analysis technique uses descriptive quantitative with SPSS 22.0 For Windows. The value of pre-test and posttest for experimental class was 68.75 and 91.75 while pre-test and posttest scores for control class were 72.25 and 83.75 respectively. From the results of pretest-posttest data analysis using T-test (hypothesis) it was found that there was a significant effect of the use of cooperative learning by GI with sacffolding models on students' physics concepts ability. These results can be shown that the Experimental class has an achievement of physics concept ability value which is significantly higher than the control class.